Business models for solar-powered irrigation in Ethiopia - International Water Management Institute (International Water Management Institute, 2018)
This brief describes three business models for smallholder solar pump irrigation in Ethiopia, each with the potential to improve agricultural production, productivity and income. The purpose of the brief is to provide prospective investors with evidence that solar pump irrigation can be both suitable and sustainable. Policymakers throughout sub-Saharan Africa, including those in Ethiopia, agree that increasing small-scale irrigation can reduce poverty and support economic growth. Limited access to the energy needed to pump water is a major constraint in most countries. Electricity is an inexpensive and efficient form of energy, but it is rarely available: only 14% of Ethiopia’s population has continuous access to electricity due to poor grid coverage and the wide dispersal of farms (World Bank 2012). The use of fossil fuel motor pumps is constrained by several factors, e.g., high operation and maintenance costs, and also results in negative environmental impacts. Solar-powered pumps offer a low-cost and environmentally-friendly alternative to electric irrigation technologies and motor pumps. Research suggests that investing in solar irrigation can profit smallholders, although the level of profit depends on the type of crops under cultivation, water delivery and application systems, and the size of the cultivated area. Other factors influencing profits include access to markets, and labor and input costs, although these are not unique to solar pump irrigation. Given the number of existing and potential motor pump users in Ethiopia – between 210,000 and 400,000 – the scope for expanding the solar pump market for irrigation appears to be significant. The Ethiopian government is committed to developing solar and other renewable energy resources, as enshrined in a range of policies, laws and regulations. The national government recently offered incentives for engaging in the solar pump sector, including access to finance, and duty and tax exemptions. Yet, there are challenges. The regional states are responsible for covering the full cost of small-scale irrigation projects, but most lack the resources and capacity to respond to farmer demand. In addition, the number of ministries, departments and agencies involved in coordinating solar energy can make it difficult for investors, importers, manufacturers and service providers to understand or respond to opportunities. While some development donors, nongovernmental organizations (NGOs) and private sector actors have already piloted solar pump projects in Ethiopia, these have not been adequate to estimate the potential market. There is a need for smart business models that present attractive opportunities for private sector investment in solar pump irrigation.